Pengaruh Kemampuan Metakognisi terhadap Hasil Belajar Matematika di SMP Negeri 2 Leuwimunding Kabupaten Majalengka - winarso, widodo (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2015)
Abstract Mathematic is the basic of science development and has the advantages in daily life. Mathematic also is saidas the queen of knowledge, because it has the important role he results of the study of mathematic influencedby internal and external factors. One of the internal factor is the ability of metacognition. For that conductedthis study aimed to determine the effect the abilit of metacognition on mathematic learning outcomes at SMPN2 leuwimunding. The method of this research is ex post facto research with a quantitative approach. Thenumber of samples in this study were 76 students who were taken by random sampling through traditionalmeans. Metacognition variables were measured using questionnaires MAI (metacognitive AwarennesInventory) which was adopted from Scraw & Dennison while studying mathematics outcome variables weremeasured using the test in the form of an essay. The technique of analysis data for hypothesis is simpleregression technique. The result of this thesis show that the result of hypothesis is tcount  = 5,489 bigger thanttable =1,993 than Ho denied and Ha accepted, it means that is influences between metacognitve on learningmath and also has the similarity of regression for that variable, that are Y=17,397 + 0, 795X, from thatsimilarity, coefficient of regression  is 0,795. It means that every improvement of metacognitive will influenceon learning student result is 0,795. Then there is the influence of metacognition ability to learn math resultswith the value of R Square of 28.9%, which means that the contribution to the ability of metacognition onlearning outcomes of mathematics is 28,9% and 71,1% is influenced by other factors.